Systematic review and meta-analysis on the etiology of bacterial pneumonia in children in sub-Saharan Africa - Chukwuemeka Onwuchekwa; Bassey Edem; Victor Williams; Ibiloye Olujuwon; Musa Jallow; Binta Sanyang; Kristien Verdonck (AOSIS, 2022)
Introduction. Before the introduction of vaccination to protect children from pneumonia, Streptococcus pneumoniae and Haemophilus influenzae type B (HiB) were the most frequent aetiological agents causing bacterial pneumonia in children under five years old. However, the etiology of childhood pneumonia appears to be changing and nonvaccine- type S. pneumoniae, non-typeable H. influenzae, and Staphylococcus aureus are becoming more relevant. Objective. We conducted a systematic review aimed at identifying the common causes of bacterial pneumonia in children in sub-Saharan Africa. Methods. We searched PubMed, Web of Science and African Index Medicus and included primary studies conducted since January 2010 that reported on the bacterial causes of pneumonia in children under five from sub-Saharan Africa. We extracted data items (about the study setting, pneumonia diagnosis, sampling, microbiological methods, and etiological agents) as well as study quality indicators.Results. Streptococcus pneumoniae was the most common bacteria in blood cultures from children with pneumonia (8%, 95% CI: 4- 14%), and H. influenzae was second (3%, 95% CI: 1-17%). Children's nasopharynx commonly contained S. pneumoniae (66%), Moraxella catarrhalis (62%), and H. influenzae (44%). Conclusion. S. pneumoniae and H. influenzae cause bacterial pneumonia in sub-Saharan African children. Our review also highlights the prevalence of potentially pathogenic bacteria in the nasopharynx of children under five and calls for more research into how nasopharyngeal colonization causes pneumonia.